Epilepsy Surgery in Young Children With Tuberous Sclerosis Complex: A Novel Hybrid Multimodal Surgical Approach. Issue 2 (10th November 2022) - Ravindra, Vijay M.; Karas, Patrick J.; Lazaro, Tyler T.; Coorg, Rohini; Awad, Al-Wala; Patino, Ilana; McClernon, Emily E.; Clarke, Dave; Cairampoma Whitehead, Laura; Anderson, Anne; Diaz-Medina, Gloria; Houck, Kimberly; et al.
Abstract : BACKGROUND: Surgery has become integral in treating children with tuberous sclerosis complex (TSC)–related drug-resistant epilepsy (DRE). OBJECTIVE: To describe outcomes of a multimodal diagnostic and therapeutic approach comprising invasive intracranial monitoring and surgical treatment and compare the complementary techniques of open resection and magnetic resonance–guided laser interstitial thermal therapy. METHODS: Clinical and radiographic data were prospectively collected for pediatric patients undergoing surgical evaluation for TSC-related DRE at our tertiary academic hospital. Seizure freedom, developmental improvement, and Engel class were compared. RESULTS: Thirty-eight patients (20 females) underwent treatment in January 2016 to April 2019. Thirty-five underwent phase II invasive monitoring with intracranial electrodes: 24 stereoencephalography, 9 craniotomy for grid/electrode placement, and 2 grids + stereoencephalography. With the multimodal approach, 33/38 patients (87%) achieved >50% seizure freedom of the targeted seizure type after initial treatment; 6/9 requiring secondary treatment and 2/2 requiring a third treatment achieved >50% freedom. The median Engel class was II at last follow-up (1.65 years), and 55% of patients were Engel class I/II. The mean age was lower for children undergoing open resection (2.4 vs 4.9 years, P = .04). Rates of >50% reduction in seizures (86% open resection vs 88% laser interstitial thermal therapy) and developmental improvement (86% open resection vs 83% magnetic resonance–guided laser interstitial thermal therapy) were similar. CONCLUSION: This hybrid approach of using both open surgical and minimally invasive techniques is safe and effective in treating DRE secondary to TSC. Clinical trials focused on treatment method with longer follow-up are needed to determine the optimal candidates for each approach and compare the treatment modalities more effectively. Abstract :